PENGGUNAAN MEDIA PEMBELAJARAN RODA IMPIAN UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA DI SMP NEGERI 217 JAKARTA - Artha, Yuni; Sujarwo, Sujarwo (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2018)
This study aims to determine the use of the dream wheel learning media to improve student learning outcomes and activeness subjects in social studies. The method used Classroom Action Research. Data collection using test and non-test techniques, in the form of tests of learning outcomes, observation and interviews. The sample or subject is class VII-A conducted in Jakarta 217 Junior High School in the second semester of 2017/2018 academic year. Based on the results of the study showed an increase in student learning outcomes of class VII-A in Jakarta 217 Junior High School. The average value of student learning outcomes in cycle 1 was obtained 67.1, cycle 2 was obtained 80.2, cycle 3 was obtained 89.2. In addition, the use of the dream wheel in social studies learning is able to increase students' activeness in terms of asking, answering, arguing and solving problems. Thus it can be concluded that the use of the learning media of the dream wheel can improve social studies learning outcomes and the activeness of class VII-A students in Jakarta 217 Junior High School.